SENYUM SAHABAT DALAM KARYA SENI GRAFIS TEKNIK STENSIL - Drs. Irwan, M.Sn., Leo Wibowo, Drs. Ariusmedi, M.Sn., (Serupa The Journal of Art Education, 2016)
Friends are places for joking and providing a positive motivation in everyday life for the author. The author feels the joy when a friend came to him. Author feels that in every step, friends were in the memory and always want to please him everywhereThe purpose of making this thesis is visualizing the friends smile in graphic art with stencil technique.The methods stage that’s going to be undertaken in the process of creation is an effort in creating works of art. The initial formation of these graphic arts consists of several stages which are the stage of alternatives sketching, developing sketches and selecting of sketches that writer has developed. After going through the election of the best sketch, writer moves the sketch to the mall in appropriate form of desired pattern.The results and the summary of the ten works of the graphic art that the authors showed are inseparable from the desire of the author for visualizing the life of the society and social environment. These works are born of idea, view, appreciation, and the author's description in facing life that’s showed in a work entitled: Flash Back, Out of the range, Behind the scenes, Throwing Toga, Hope, smile, Coffeeeee, Sunset, Options, the hum song.Based on the results and the summary of the ten works of graphic art that the authors show, it is inseparable from the desire of the author to visualize the life of the society and social environment. These works are born of idea, view, appreciation, and the author's description in facing life.Key word : The friends smiling in the graphic art stencil technique